The Priority of the Family-centered Role in Combating the Prevalence of COVID-19 Epidemic in Iran - Mousa Bamir Bamir; Salman Farahbakhsh; Salman Daneshi (Shiraz University of Medical Sciences, 2022)
Coronaviruses are relatively old viruses that first were identified in 1930 as the infectious bronchitis virus in birds, and in 1940 were identified as the cause of gastroenteritis in pigs. Global concern rising about mortality during the COVID-19 pandemic and varieties of clinical signs seems to be a good reason to consider using COVID-19 to fight the virus before becoming infected. According to the unprecedented transmission rate of infectious viruses from the past and the evidence of the effectiveness of using preventive methods in the fight against infectious and respiratory diseases, we use the prominence of the family-centered role in Iran compared to other countries (1,2) Following the globalization crisis of COVID-19 in different parts of the world, Iran was facing a more destructive virus, increasing the most brutal sanctions pressure of the United States which has many effects and challenges. In particular, the medical sector faced severe challenges and problems which is referred as drug terrorism to some extent (4,5) Sanctions caused barriers for importing humanitarian aid and medical supplies, including coronavirus detection tools, providing necessary medicines and raw materials to give citizens access the information about the disease and its prevalence.   In such a situation, the country's health sector needs to take preventive measures to reduce transmission risk and manage disease. One of the most important ways to prevent the transmission is maintaining the social distance and home care (family-oriented) which are among the most cost-effective ways to reduce vulnerabilities to Covid-19. Domestic and family-oriented policies and quarantine measures controled the speed transmission in East Asian countries. Their similar cases and  useful experiences can be a  successful scientific and experimental model for Iran, where needs such a control policy more than other countries. Overall, although living in home quarantine has psychological, social, and economic consequences, in Iran, the first and most important strategy for using a preventive home care policy is to focus on people's culture. Increasing training activities, familirizing people with the proper personal and social health behavior, changing people's attitudes towards the adoption of social spacing and justifying why staying at home can be very effective and helpful. Proper and principled policies by the government, such as promoting e-commerce infrastructure and encouraging people to shop online, providing livelihood support to low-income people, Controlling rumors and preventing the spread of false news and unscientific therapies, controlling anxiety and stress management by creating creativity and innovation for fun and vibrancy to avoid psychological and social challenges in the community in this condition are effective and useful strategies (6).